Microwave‐assisted cleavage of Alloc and Allyl Ester protecting groups in solid phase peptide synthesis. (8th August 2016) - Wilson, Krista R.; Sedberry, Seth; Pescatore, Robyn; Vinton, Daniel; Love, Brian; Ballard, Sarah; Wham, Bradley C.; Hutchison, Stacy K.; Williamson, Eric J.
Abstract : Orthogonal protection of amino acid side chains in solid phase peptide synthesis allows for selective deprotection of side chains and the formation of cyclic peptides on resin. Cyclizations are useful as they may improve the activity of the peptide or improve the metabolic stability of peptides in vivo . One cyclization method often used is the formation of a lactam bridge between an amine and a carboxylic acid. It is desirable to perform the cyclization on resin as opposed to in solution to avoid unwanted side reactions; therefore, a common strategy is to use –Alloc and –OAllyl protecting groups as they are compatible with Fmoc solid phase peptide synthesis conditions. Alloc and –OAllyl may be removed using Pd(PPh3 )4 and phenylsilane in DMF. This method can be problematic as the reaction is most often performed at room temperature under argon gas. It is not usually done at higher temperatures because of the fear of poisoning the palladium catalyst. As a result, the reaction is long and reagent–intensive. Herein, we report the development of a method in which the –Alloc/–OAllyl groups are removed using a microwave synthesizer under atmospheric conditions. The reaction is much faster, allowing for the removal of the protecting groups before the catalyst is oxidized, as well as being less reagent–intensive. This method of deprotection was tested using a variety of amino acid sequences and side chain protecting groups, and it was found that after two 5‐min deprotections at 38°C, all –Alloc and –OAllyl groups were removed with >98% purity. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Palladium‐catalyzed deprotection of Alloc‐protected amines and OAllyl‐protected carboxylic acids in solid phase peptide synthesis is accomplished in high purity using a microwave synthesizer. The reaction is performed in an open vessel and is faster with a reduction in expensive and hazardous reagents.